Dual-role Conflict among Female Primary School Teachers - Lawal Abdul Faragai (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2017)
This paper is a conceptual approach that stimulate able scholars that failed to ponder carefully on dual-role conflict among female primary school teachers. Of course, female primary school teachers are experiencing dual-role conflict. Also, presently female primary school teachers has dominated our primary schools teaching our children, on the same vain experiencing dual-role conflict which needed urgent attention from all stakeholders. The essence of this paper was due to the relevance of work and family matters. Scholars are really trying their best for enlightening all stakeholders on the issue of work-family role conflict in many discipline. In Education, related researches are always carrying on but the background level of education primary school is somehow been put aside with little concern. Considering this will help in making the work-life balance of female primary school teachers more sustainable. With this teaching and learning of our younger children would be efficient and effective. The researcher has proposed a conceptual framework in studying dual-role conflict among female primary school teachers. However, the qualitative interpretivist approach using case study or grounded theory would be applicable in conducting such type of research respectively.